Fluid mechanics a short course for physicists - Falkovich, G. 1958- (Cambridge University Press, 2011)
"The multidisciplinary field of fluid mechanics is one of the most actively developing fields of physics, mathematics and engineering. In this book, the fundamental ideas of fluid mechanics are presented from a physics perspective. Using examples taken from everyday life, from hydraulic jumps in a kitchen sink to Kelvin-Helmholtz instabilities in clouds, the book provides readers with a better understanding of the world around them. It teaches the art of fluid-mechanical estimates and shows how the ideas and methods developed to study the mechanics of fluids are used to analyze other systems with many degrees of freedom in statistical physics and field theory. Aimed at undergraduate and graduate students, the book assumes no prior knowledge of the subject and only a basic understanding of vector calculus and analysis. It contains 32 exercises of varying difficulties, from simple estimates to elaborate calculations, with detailed solutions to help readers understand fluid mechanics"-- Provided by publisher.
Machine generated contents note: 1. Basic equations and steady flows; 2. Unsteady flows; 3. Dispersive waves; 4. Epilogue; 5. Solutions; References; Index.
Keywords: Fluid mechanics.; elektronické knihy; electronic books